2012
DOI: 10.1590/s0034-737x2012000600008
|View full text |Cite
|
Sign up to set email alerts
|

Expressão de caracteres de tubérculos em função do tamanho de recipiente usado no cultivo de batata na geração de plântulas

Abstract: Expression of tuber traits as a function of pot size used to grow potato seedlingsIn potato breeding, the exclusion of inferior genotypes by selection in early generations provides more versatility and cost reduction. The objective of this study was to evaluate the influence of pot size on the expression of tuber traits in potato families grown as seedling generation. Ten potato families were planted in two pot sizes, large (1 L) and small (250 ml), in the greenhouse. The following tuber traits were evaluated:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
1
3
0
1
Order By: Relevance
“…Thus, it would not be advisable to undertake family selection for tuber yield in the FCG in the greenhouse using small diameter pots. This result is corroborated by the study of Verissimo et al (2012) who studied the influence of small pot size on the expression of tuber traits in potato families in the SG. These authors observed that pots with 1 L capacity allowed greater expression of production traits in comparison with pots of 0.25 L capacity and, consequently, they allowed better estimates of genetic variability among the families.…”
Section: Selection Among Familiessupporting
confidence: 55%
“…Thus, it would not be advisable to undertake family selection for tuber yield in the FCG in the greenhouse using small diameter pots. This result is corroborated by the study of Verissimo et al (2012) who studied the influence of small pot size on the expression of tuber traits in potato families in the SG. These authors observed that pots with 1 L capacity allowed greater expression of production traits in comparison with pots of 0.25 L capacity and, consequently, they allowed better estimates of genetic variability among the families.…”
Section: Selection Among Familiessupporting
confidence: 55%
“…Plântulas oriundas de sementes botânicas, comparadas às provenientes de tubérculos-semente, não apresentam uma fonte extra de energia para impulsionar o crescimento inicial, estando na dependência de condições favoráveis do ambiente (Lommen, 1999). No entanto, a utilização da geração plantular, definida neste estudo como G1, se justifica pela possibilidade de avaliar um grande número de indivíduos por unidade de área (~177 indivíduos por m 2 ), sem que haja limitação ao crescimento dos tubérculos, o que proporcionaria melhor expressão de caracteres de aparência e rendimento dos tubérculos de batata (Verissimo et al, 2012). Além disso, as condições ambientais são mais uniformes, pois os minitubérculos são produzidos em casa de vegetação, em sistema fechado de cultivo utilizando areia grossa como substrato e fertirrigação, o que minimiza a variância ambiental.…”
Section: Resultsunclassified
“…The lower number of tubers, of smaller size, has been indicated as the main obstacle for the application of selection during seedling generation (BROWN et al, 1984;PINTO, 1999;GOPAL;MINOCHA, 1997). Recent studies have focused on the size of the containers where the seedling is grown, and for some traits, the containers should be larger than the usual 250 ml vases used in many potato improvement programs (VERÍSSIMO et al, 2012). In the seedling generation, families could not be clustered using the traits NTU, MAS and AMA.…”
Section: Resultsmentioning
confidence: 99%